Implementation Of Curriculum Monitoring and Evaluation in Schools - Marlina, Marlina; Mardiana, Ratna (Indonesian Journal Education, 2023)
Curriculum is an important thing in education. The curriculum has a central position in the entire educational process. The curriculum is a learning program so that educational goals are achieved, besides that the curriculum is also a guideline for implementing learning at all types and levels of education. Therefore, it is necessary to monitor and evaluate regularly, plan and systematically collect and process information and make decisions regarding curriculum implementation in schools. Monitoring and evaluation are two things that are similar but not the same, but both require the same elements and tools, including a clear program, targets and indicators, and a database containing up-to-date data